A Releitura de O Leão, a Feiticeira e o Guarda-Roupa no Cinema - Brion, Nicolai Henrique Dianim (2013)
The Lion, the Witch and the Wardrobe (1950), by C. S. Lewis, is a typical fantasy narrative. Thus, its form and contents are shaped by characteristics which have traditionally marked the genre, such as the appeal to a medieval atmosphere. The story was adapted to the Hollywood cinema by Andrew Adamson in 2005 keeping the same title. The main goal of this dissertation is to discuss the strategies employed by the director to produce an action blockbuster in the format of the classical Hollywood narrative through the exploration of the fantastic and medieval elements of the novel. It starts from the idea that the film adaptation, although it comes from a text which occupies a peripheral position in the British literary system, manages to stand out in the Hollywood cinematographic system. This research is descriptive and has a qualitative approach, which consists of the reading of both the novel and the film to analyse how fantasy and medievalism are configured in these narratives. The analysis led us to conclude that the adaptation was able to resignify the elements of the novel which are responsible for its marginalization. The theoretical bases for this work are the principles of the descriptive translation studies, especially the concept of rewriting, by Lefevere (2007), and the premises of the polysystem theory, by Even-Zohar (1990). Theoretical references still include Todorov (2010, 2006) and Propp (2006), to characterize the novel as a fantasy narrative; Cecire (2009) and Hobsbawm (1997), to approach the matter of medievalism; Compagnon (1999) and Wellek and Warren (2003), to discuss the literary canon; and Bordwell (1985), to delimitate the properties of the classical Hollywood narration pattern.